2009
DOI: 10.1002/jor.20956
|View full text |Cite
|
Sign up to set email alerts
|

Thymosin beta‐4 directs cell fate determination of human mesenchymal stem cells through biophysical effects

Abstract: Change of actin filament organization at the early stage of cell differentiation directs cell fate commitment of mesenchymal stem cells (MSCs). Thymosin beta-4 (Tb 4 ), a major G-actin sequestering peptide, is known to regulate the cytoskeleton. The study investigated the ways in which Tb 4 regulates cell fate determination in MSCs upon differentiation induction. It was found that Tb 4 decreased F-actin formation, reduced the F-actin/G-actin ratio, and inhibited osteogenic differentiation; such actin reorganiz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(5 citation statements)
references
References 26 publications
0
5
0
Order By: Relevance
“…These data demonstrate that ridges and grooves as low as 400 nm pitch modify alignment and/or morphology of hMSCs. It is known that changes in cell morphology affect gene expression profiles and cell differentiation [3133]. In particular, hMSCs differentiate into osteoblasts when allowed to spread and flatten, whereas restricting the surface area upon which to grow promotes adipogenic differentiation of hMSCs [4].…”
Section: Discussionmentioning
confidence: 99%
“…These data demonstrate that ridges and grooves as low as 400 nm pitch modify alignment and/or morphology of hMSCs. It is known that changes in cell morphology affect gene expression profiles and cell differentiation [3133]. In particular, hMSCs differentiate into osteoblasts when allowed to spread and flatten, whereas restricting the surface area upon which to grow promotes adipogenic differentiation of hMSCs [4].…”
Section: Discussionmentioning
confidence: 99%
“…It has been suggested that Tβ4 is a novel signaling molecule, which activates various cell type differentiation [15,16,21,31]. However, its role in the differentiation of ES or adult stem cells into cardiac myocytes has not been examined.…”
Section: Discussionmentioning
confidence: 99%
“…Tβ4 plays a role in human bone marrow-derived MSC differentiation. Tβ4 is known to suppress osteogenic differentiation by sequestering G-actin and preventing its polymerization [ 23 ]. It has shown a biophysical effect using exogenous Tβ4, without altering gene expression, measured by monitoring Runt-related transcription factor 2 (Runx2) and peroxisome proliferator-activated receptor gamma (PPARγ) genes during early osteogenic differentiation.…”
Section: Mechanotransduction and Cytoskeletal Rearrangement Duringmentioning
confidence: 99%
“…Despite a lack of change in gene expression, one cannot rule out the possibility of alteration in other genes not included in this study, since alteration in the actin cytoskeleton may modify gene expression via mechanotransduction. On the other hand, this study has shown that in these conditions, the adipogenic differentiation was promoted, but chondrogenic differentiation was not altered, pointing out the difference in requirements and importance of F-actin during these processes [ 23 ].…”
Section: Mechanotransduction and Cytoskeletal Rearrangement Duringmentioning
confidence: 99%